Permian-Triassic evolution of Tethys and western circum-Pacific - Yin, Hongfu (Elsevier, 2000)
Permian and Triassic are the interval known for the integration and separation of Pangea, the closure of the Palaeotethys and the opening of Mesotethys. They were associated with a series of worldwide events including the Late Palaeozoic glaciation and succeeding extensive evaporatic and reef formations, the end-Palaeozoic regression, strong orogenies and widespread volcanism and magmatism, and finally, the Permo-Triassic biotic macro-extinction. These events resulted in the formation of enormous reserves of coal, petroleum, evaporites, phosphorites and metal resources. The Permian and Triassic thus constitutes a time interval particularly important both for understanding the Earth's history and for exploration of mineral resources. The book aims to reconstruct the Permian-Triassic history of Pangea, Palaeo-Tethys and Palaeo-Pacific through stratigraphic, palaeogeographic and other interdisciplinary approaches. It consists of two parts. Part 1 deals with regional stratigraphy of Tethyan and western Circum-Pacific countries which is the basis for interregional correlation, and palaeogeography. Part 2 deals with the biotic evolution at the Permian-Triassic transition, focusing on the major invertebrate groups: foraminifers, radiolarians, brachiopods, ammonoids and conodonts.
"Supported by the National Science Foundation of China (NSFC) project no. 49632070."
Keywords: Tethysmeer.; Perm.; elektronické knihy; electronic books; From 190 to 280 million years ago; Geology, Stratigraphic -- Permian.; Geology, Stratigraphic -- Triassic.; Tethys (Paleogeography)